Historia y memorias de la posguerra. Paracuellos y el recuerdo del Auxilio Social - Ángela Cenarro; Elena Masarah (Cahiers de Civilisation Espagnole Contemporaine)
The falangist «Auxilio Social» was a space in which the unequal and hierarchical power relationship between the victors and the defeated at the end of the Spanish Civil War was brutally expressed. In its most emblematic institution, the children’s homes, the children of the Republicans and the victims of war, reprisals or exile, as well as those of families devastated by destitution in the post-war, should become «active servants of a fair Spain». The comic Paracuellos, by Carlos Giménez, is a representation of the author’s experiences in these homes that has served to convey the memories of those who were children of the Auxilio Social and denounce the abuses committed against them. Likewise, since its publication in 1977, it has favoured the inclusion of experiences marginalized by the dominant accounts in the collective memory of the Civil War and the post-war period.